Perilaku Petani di Sekitar Hutan Lindung Soputan dan Manimporok Kecamatan Ratahan Kabupaten Minahasa Tenggara - Palmarum M. Masalamate; Olfie L.S. Benu; Caroline B.D. Pakasi (COCOS, 2015)
ABSTRACT Palmarum Marvel Masalamate. The Farmers Behavior around Soputan and Manimporok Protected Forest, with the adviser Benu Olfie L.S,. as the chief, Caroline B.D. Pakasi. as the member.      The purpose of this research is to determine the behavior of farmers in managing the agricultural area around Soputan and Manimporok protected forest in Kalatin village in the township of North Lowu, district of Ratahan.  This research was conducted for two months from May to Juny 2015.Data collection used survey method which the data was from primary and secondary data.  The sampling used purposive sampling method to 24 respondents (30%) from 80 leaders of family who work as farmers in Kalatin village.From the analysis results obtained many respondents understand the knowledge of the protected forest, well management in agricultural area, and at every level of the respondent action against protected forest, all respondents stated that will help to develop the conservation of protected forest.  Based on the results above, it can be concluded that the farmers in Kalatin village have good behavior and do not spoil in managing and maintaining agricultural area in Soputan and Manimporok protected forest.  Keywords: Behavior, Farmers, Protected Forest.